Crystal structures of Plasmodium falciparum cytosolic tryptophanyl-tRNA synthetase and its potential as a target for structure-guided drug design - Koh, Cho Yeow (2013)
Malaria, most commonly caused by the parasite Plasmodium falciparum, is a devastating disease that remains a large global health burden. Lack of vaccines and drug resistance necessitate the continual development of new drugs and exploration of new drug targets. Due to their essential role in protein synthesis, aminoacyl-tRNA synthetases are potential anti-malaria drug targets. Here we report the crystal structures of P. falciparum cytosolic tryptophanyl-tRNA synthetase (Pf-cTrpRS) in its ligand-free state and tryptophanyl-adenylate (WAMP)-bound state at 2.34 Å and 2.40 Å resolutions, respectively. Large conformational changes are observed when the ligand-free protein is bound to WAMP. Multiple residues, completely surrounding the active site pocket, collapsed onto WAMP. Comparison of the structures to those of human cytosolic TrpRS (Hs-cTrpRS) provides information about the possibility of targeting Pf-cTrpRS for inhibitor development. There is a high degree of similarity between Pf-cTrpRS and Hs-cTrpRS within the active site. However, the large motion that Pf-cTrpRS undergoes during transitions between different functional states avails an opportunity to arrive at compounds which selectively perturb the motion, and may provide a starting point for the development of new anti-malaria therapeutics.